Respuesta :
Given expression: [tex]\left(4y^2\right)^3\left(3y^2\right)[/tex].
[tex]\mathrm{Apply\:exponent\:rule}:\quad \left(ab\right)^c=a^cb^c[/tex]
[tex]\left(4y^2\right)^3=4^3\left(y^2\right)^3[/tex]
[tex]\mathrm{Apply\:exponent\:rule}:\quad \left(a^b\right)^c=a^{bc}[/tex]
[tex]\left(y^2\right)^3=y^{2\cdot \:3}=y^6[/tex]
[tex]\left(4y^2\right)^3\cdot \:3y^2=4^3y^6\cdot \:3y^2[/tex]
[tex]\mathrm{Apply\:exponent\:rule}:\quad \:a^b\cdot \:a^c=a^{b+c}[/tex]
[tex]y^6y^2=\:y^{6+2}=\:y^8[/tex]
[tex]=4^3\cdot \:3y^8[/tex]
[tex]=192y^8[/tex]